Religious freedom and mass conversion in India - Dudley-Jenkins, Laura (Pennsylvania studies in human rights., 2019)
Religious Freedom and Mass Conversion in India argues that, although the right to religious freedom is enshrined in India's constitution, mass conversions to minority religions have complicated the practice of this right, which is increasingly invoked to restrict, rather than defend, the freedoms of minorities and women.